A case of recurring spinal ependymoma in 37-years old man after surgery and adjuvant therapy - Anđelić, Nikola; Šćepanović, Bojana; Salma, Svetlana; Kozić, Duško; Prvulović Bunović, Nataša (Archive of Oncology, 2020)
We present the case of a 39-years old man who underwent three surgeries because of spinal ependymoma located in cauda equina region. He presented at the Oncology Institute of Vojvodina for combined adjuvant chemo- and radiotherapy after the second surgery. An MRI examination performed after six cycles of therapy showed no signs of disease. 26 months later, a follow-up MRI showed recurrence of disease in the form of small drop metastasis. Six months later, the patient underwent the third surgery. The patient is currently receiving another cycle of radiotherapy, and is scheduled for additional cycles of chemotherapy. Ependymomas are the most common spinal cord malignancy in adults. The symptoms are nonspecific which often causes a delay in diagnosis. An MRI examination of the spine with contrast admission is the study of choice for detecting spinal cord masses. Surgery is the first-line therapy for ependymomas. Recurrence rate is associated with the extent of surgical resection, with en bloc and gross-total resection being associated with lower rates of disease recurrence. In children under 3 years, adjuvant chemotherapy is advocated, while older children and adults undergo adjuvant radiotherapy or combined chemo- and radiotherapy in cases of subtotal resection or tumor recurrence.
Keywords: Ependymoma; Adult; Spinal; Surgery; Recurrence; Radiotherapy